IMPACT OF PROBLEM-BASED LEARNING IN DEVELOPING LOGICAL AND ANALYTICAL THINKING SKILLS OF SRI LANKAN UNDERGRADUATES. (Proceedings of the International Conference on Future of Education, 2019)
Problem-based Learning (PBL) is a prominent language learning method, where real-life matters of the learners are used as ‘problem situations’ in developing many relevant life skills. Despite Sri Lanka marking a high literacy rate in Asia, it lies behind the average IQ scale in the world. It is observed that the competitive education system does not encourage learners to develop their cognitive abilities and other soft skills. This research was aimed to find out the effectiveness of PBL in enhancing logical and analytical thinking skills. Its objectives were to study the influence of PBL in language education and to find out if logical and analytical thinking abilities be enhanced through PBL. The research took an experimental design. The target population consisted of 60 randomly selected undergraduates of a Sri Lankan University. A special module prepared by the researcher, based on developing cognitive skills of the undergraduates, was tested on the population. A pre and a post ‘spot-test’ on critical thinking was given and the answers were individually analyzed to see the impact. 10 undergraduates were interviewed to get the student perspective of PBL. It was confirmed that not only the analytical and logical thinking abilities, but also other cognitive skills such as critical thinking, justification skills as well as language skills could be developed through PBL.Keywords: Problem-based Learning, Logical thinking, Analytical thinking, Cognitive skills, spot-test
Keywords: ELT; PBL; Logical thinking; cognitive skills